Savanna Rodents’ Selective Removal of an Encroaching Plant’s Seeds Increased With Grass Biomass - Teman, Sarah J.; Stevens, Nicola; Monadjem, Ara; Fletcher, Robert J.; Austin, James D.; McCleery, Robert (Frontiers in Ecology and Evolution, 2021)
In savannas across the planet, encroaching woody plants are altering ecosystem functions and reshaping communities. Seed predation by rodents may serve to slow the encroachment of woody plants in grasslands and savannas. Our goals for this study were to determine if rodents in an African savanna selectively removed seeds of an encroaching plant and if foraging activity was influenced by the local vegetation structure or by the landscape context. From trials with two species of seeds (encroacher = Dichrostachys cinerea, non-encroaching overstory tree = Senegalia nigrescens) at 64 seed stations, we recorded 1,065 foraging events by seven species of granivorous rodents. We found a strong positive relationship between rodent activity and the number of seeds removed during trials. Foraging events were dominated by rodent seed predators, with < 10.6 % of events involving a rodent with the potential for secondary dispersal. Rodents selectively removed the seeds of the encroaching species, removing 32.6% more D. cinerea seeds compared to S. nigrescens. Additionally, rodent activity and the number of seeds removed increased at sites with more grass biomass. Our results suggest a potential mechanistic role for rodents in mitigating the spread of woody plants in grass dominated savannas.